2018
DOI: 10.1007/s10911-018-9416-0
|View full text |Cite|
|
Sign up to set email alerts
|

The Emerging Roles of Steroid Hormone Receptors in Ductal Carcinoma in Situ (DCIS) of the Breast

Abstract: Ductal carcinoma in situ (DCIS) is a non-obligate precursor to most types of invasive breast cancer (IBC). Although it is estimated only one third of untreated patients with DCIS will progress to IBC, standard of care for treatment is surgery and radiation. This therapeutic approach combined with a lack of reliable biomarker panels to predict DCIS progression is a major clinical problem. DCIS shares the same molecular subtypes as IBC including estrogen receptor (ER) and progesterone receptor (PR) positive lumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 104 publications
0
9
0
Order By: Relevance
“…Dean Edwards presented a ductal carcinoma in situ (DCIS) model using MCF10 DCIS.COM cells engineered with lentiviral vectors to stably express ERalpha, PR-A, and PR-B. Based on gene expression profiling, these cells resemble luminal breast cancer subtypes and are robustly responsive in cell culture to either estrogen or progesterone in terms of regulation of known target genes (57). The cells have also been used successfully in the mouse mammary intraductal xenograft (MIND) system and are responsive to estrogen and progesterone in vivo.…”
Section: New Models To Study Progesterone Action In Ductal Carcinoma mentioning
confidence: 99%
“…Dean Edwards presented a ductal carcinoma in situ (DCIS) model using MCF10 DCIS.COM cells engineered with lentiviral vectors to stably express ERalpha, PR-A, and PR-B. Based on gene expression profiling, these cells resemble luminal breast cancer subtypes and are robustly responsive in cell culture to either estrogen or progesterone in terms of regulation of known target genes (57). The cells have also been used successfully in the mouse mammary intraductal xenograft (MIND) system and are responsive to estrogen and progesterone in vivo.…”
Section: New Models To Study Progesterone Action In Ductal Carcinoma mentioning
confidence: 99%
“…According to histopathological point of view, 80% of the breast tumors are ductal tumors and 10-15% is invasive lobular carcinoma (ILC) [1]. The most important markers have characterized by IHC-based tumor markers in BC, considering three main hormone receptors, including ER, PR and, HER2 [11]. Retrospective studies have demonstrated that patients with ER-and/or PR-containing tumor cells tend to have a better outcome than those without the receptors [11].…”
Section: Discussionmentioning
confidence: 99%
“…Mammaglobin (MAM) is a protein found in mammary tissue and in the serum, as well. MAM has been proposed as a biomarker to diagnose BC, given that patients exhibit an increased amount of the protein in their serum and tumor tissue compared with healthy individuals [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Human DCIS.com cells 24 were engineered to express both ER and PR, and the cell line has been previously characterized as an in vitro model of luminal DCIS that is highly responsive to both estrogen and progesterone. 25 ER and PR are ligand-dependent steroid receptor nuclear transcription factors that act primarily to regulate expression of gene networks. They also mediate rapid effects of steroid hormones on extranuclear proteinsignaling pathways through alteration of protein kinase activity and phosphorylation of protein substrates and downstream events.…”
Section: Effects Of Steroid Hormones On Protein-signaling Pathways In Breast Cancer Cellsmentioning
confidence: 99%